Spinal cord involvement in MOGAD, AQP4-Ab NMOSD & MS. Issue 6 (27th May 2022) - Mariano, Romina; Messina, Silvia; Roca-Fernandez, Adriana; Cavey, Ana; Everett, Rosie; Leite, Maria Isabel; Kong, Yazhuo; Palace, Jacqueline
Abstract : Introduction: Spinal cord involvement is important in aquaporin-4(AQP4) antibody(Ab)-positive neuro- myelitis optica spectrum disorder(NMOSD), myelin-oligodendrocyte glycoprotein-Ab disease(MOGAD) and multiple sclerosis(MS). Methods: Data from adults with spinal cord involvement and MOGAD(n=46) or AQP4-Ab(n=69) were retrospectively analysed. An additional c-spine MRI (3DT1, 3DT2, 2D axial T2*, DTI, MTR) was performed and analysed using SCT and FSL on 20 patients from each cohort, together with 20 MS and 20 healthy volunteers(HV). Results: Compared to AQP4-Ab, MOGAD patients had more short lesions(p≤0.0001) and multiple lesions(p≤0.001). In AQP4-Ab, age was the most important factor affecting long-term outcome; while in MOGAD it was the presence of a brainstem lesion at the time of the myelitis. In the cervical cord MRI study, the MOGAD group had no residual lesions, and did not show a significant reduction in either CSA, FA or MTR, but showed a reduction of grey matter volume in those with cervical cord involvement(p=0.0229). The AQP4-Ab group showed a significantly reduced CSA(p=0.0288) and FA(p=0.0085) and a reduced MTR compared to both HV(p≤0.0001) and MOGAD(p=0.0096). This was driven by those with cervical cord lesions. The MS group had a significantly reduced FA(p=0.0204), GM(p=0.0133) and MTR(p=0.0106). FA associated with EDSS(p=0.02, R2=0.25) in the corticospinal tract and pain in the spinothalamic tract(p≤0.01, R2=0.32). Overall, CSA was the strongest predictor of EDSS. Conclusion: MOGAD may predominantly affect the grey matter. AQP4-Ab disease shows the most severe, localised cord damage. MRI metrics do not discriminate these conditions but show clinical significance. romina.mariano@ndcn.ox.ac.uk